L1: Targeting and scaling out - Barron, Jennie; Chadwick, Matthew; Cinderby, Steve; Kemp Benedict, Eric; Kongo, Victor; Noel, Stacey (2010)
Despite hosting some of the most developed sub Saharan countries, a majority of rural smallholder farmers in the Limpopo basin still live in poverty. The challenge of low and highly variable rainfall together with inadequate technology transfers, inadequate policy and investment context all act to disable successful transitions out of poverty. The CPWF Phase I identified several opportunities to manage rainfall in more efficient and productive manners at field to basin scales. The challenge of successful targeting and scaling out is still a key research and development area to contribute towards the Limpopo development challenges with opportunities to enable transformations of rural livelihoods at a greater scale. The project L1 ”Targeting and scaling out” aims to develop an evidence and knowledge-based tool that will map the likelihood that a given intervention will be successful in given locations. The tool would be intended for non-expert users and would be available via the World Wide Web. The proposed L1 project will contribute to achieving the BDC challenge of improving rainwater and small reservoir management to contribute to poverty reduction and improved livelihoods resilience. It will do this by producing a framework and web-based and electronic “decision support”, (or targeting and scaling out tool) that will identify likely sites to introduce AWM interventions for smallholder farming systems.